Development of random mating population for genetic enhancement of yield traits in sunflower (Helianthus annuus L.): Development of random mating population for genetic enhancement of yield traits in sunflower (Helianthus annuus L.) - H P MEENA; PRADUMAN YADAV; LAKSHMI PRAYAGA; A VISHNUVARDHAN REDDY (Journal of Oilseeds Research, 2020)
As in any crop, in sunflower, to develop improved breeding lines having superior yield, oil content and resistant to biotic and abiotic stresses, it is essential to have genetically diverse parental lines. In this study, we used six trait specific inbred lines and allowed random mating in isolation. Through population improvement a total of 150 new restorer lines have been developed. Significant variation was observed for different traits among the lines studied. The progenies RGP-11-P1-S2 (39.89%), RGP-58-P4-S2 (39.31%), RGP-58-P4-S1-1 (39.31%) were promising for oil content. RGP-58-P4-S2 (32.1 g/plant), RGP-85-P1-S1 (31.3 g/plant), RGP-85-P1 (30.1 g/plant) for high seed yield. Based on survival under stress condition, the progenies RGP-21-P5, RGP-21-P6, RGP-32-P1 and RGP-61-P2 were identified as best genotypes under moisture stress conditions. RGP-21-P4-S1-3 and RGP-50-P2-S1 were completely free from powdery mildew.